1990
DOI: 10.1177/000992289002900207
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Breast-feeding Patterns Established in the Hospital

Abstract: Data from a national survey of new mothers were analyzed to determine the effect that demographic characteristics, breast-feeding instructions, and infant formula discharge kits had on breast-feeding patterns established in the hospital. Results indicated that mothers who exclusively breast-fed their infant were more likely to be affluent, college educated, and not working outside the home. Mothers who exclusively breast-fed their infants in the hospital and subsequently practiced partial breast-feeding or for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This study shows results similar to those obtained in other countries regarding other possible factors predicting breast-feeding (4,5,(10)(11)(12)(13)(14). Older women do breast-feed their babies longer than the younger ones, and in this study it was more likely that mothers breast-fed their second baby longer than the first one.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study shows results similar to those obtained in other countries regarding other possible factors predicting breast-feeding (4,5,(10)(11)(12)(13)(14). Older women do breast-feed their babies longer than the younger ones, and in this study it was more likely that mothers breast-fed their second baby longer than the first one.…”
Section: Discussionsupporting
confidence: 90%
“…The present investigation showed that infants in Iceland are breast-fed as long as or longer than in other developed countries (4,5,(10)(11)(12). This trend is probably the result of the increasing propaganda for breast-feeding and maintaining good health as well as education by health personnel and support for breast-feeding.…”
Section: Discussionmentioning
confidence: 47%
“…Although not well identified in the literature, parity does seem to play a role in the duration of breastfeeding. Findings from several studies suggest that multiparous women breastfeed longer when compared to primiparous women (Hawkins et al, 1987;Jones et al, 1986;Ryan, Wysong, Martinez, & Simon, 1990;Whichelow, 1982). Parity was significantly related to an increased duration of breastfeeding at 16 weeks' postpartum, but not at 12 and 20 weeks' (West, 1980).…”
Section: Breastfeeding Duration and Paritymentioning
confidence: 99%
“…Demographic characteristics positively associated with breastfeeding include non-African American ethnicity (6,7), higher educational attainment (8,9), older maternal age (6,8), and being married (8,10). However, inconsistent, incomplete, and incon-clusive information exists regarding the relationship between breastfeeding intention and parity (6,(11)(12)(13)(14)(15), earlier use of prenatal care services (16), and previous breastfeeding experience (14).…”
mentioning
confidence: 99%